EKRANISASI CERPEN “الأسد الجائع” KE DALAM FILM “الأسد الجائع” KARYA QISHASHU AL JADDAH - Rofiqi Rofiqi (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2025)
Whitewashing of written literary works is a common occurrence in society these days. This practice is commonly referred to as "whitewashing" or "ecranization" of written works. This article compares the plotlines of the short story and the movie "Al Asadu Al Jai’” and identifies the alterations that the ecranization process brought forth in the film, which is available on the Qishashu Al Jaddah YouTube channel. This study uses ecranization theory to analyze its descriptive qualitative data. Albir Muthlaq's short story " Al Asadu Al Jai’" and the movie " Al Asadu Al Jai’" from the Qishashu Al Jaddah YouTube channel are the sources of the data. The findings of this study included the identification of variations in the story's characters, setting, and plot. Story elements can be moved, added, or shrunk in this way.